Sandworm : a new era of cyberwar and the hunt for the Kremlin's most dangerous hackers - Greenberg, Andy (Doubleday, 2019)
"In 2014, the world witnessed the start of a mysterious series of cyberattacks. Targeting American utility companies, NATO, and electric grids in Eastern Europe, the strikes grew ever more brazen, including the first-ever blackouts triggered by hackers. They culminated in the summer of 2017, when the malware known as NotPetya was unleashed, penetrating, disrupting, and paralyzing some of the world's largest companies--from drug manufacturing to software to shipping. At the attack's epicenter in Ukraine, ATMs froze. The railway and postal systems shut down. Hospitals went dark. NotPetya spread around the world, inflicting an unprecedented ten billion dollars in damage--the largest, most devastating cyberattack the world had ever seen. The hackers behind these attacks are quickly gaining a reputation as the most dangerous team of cyberwarriors in history: Sandworm. Working in the service of Russia's military intelligence agency, they represent a persistent, highly skilled, state-sponsored force, one whose talents are matched by their willingness to launch broad, unrestrained attacks on the most critical infrastructure of their adversaries. They target government and private sector, military and civilians alike. A chilling, globe-spanning detective story, Sandworm considers the danger this force poses to our national stability and security. As the Kremlin's role in meddling in the 2016 election, manipulating foreign governments, and sparking chaos comes into greater focus, Sandworm exposes the realities not just of Russia's global digital offensive, but of an era where warfare ceases to be waged on the battlefield. It reveals how the line between digital and physical conflict, between wartime and peacetime, have begun to blur--with world-shaking implications"-- Provided by publisher